Profil Kemampuan Literasi Sains Peserta Didik di Salah Satu SMA Negeri Kota Sragen: Profile of Students' Scientific Literacy Ability in One of the State Senior High Schools of Sragen City - Bagasta, Adifa Risa; Rahmawati, Dewi; M, Dzahra Mar’atul F. Y.; Wahyuni, Indah Purbo; Prayitno, Baskoro Adi (Pedagogia : Jurnal Pendidikan, 2018)
Literacy of science is a problem in Indonesia because of the low scientific literacy ability according to PISA. The objective of this research is to know the ability of science literacy ability of one of SMA Negeri in Sragen city. The research used survey research type with quantitative descriptive approach. The population in the study consisted of 5 classes of X IPA and 5 classes of XI IPA of 300 students. The sampling technique uses proportionate stratified random sampling. The sample was taken 10% of the population of 30 students consisting of 15 children class X IPA and 15 children class XI IPA. The literacy ability of learner’s science is measured using multiple choice tests developed by Rizkita et al. (2016). Research data were analyzed using quantitative descriptive analysis. The results showed the ability of science literacy learners based on the indicator that is the scientific opinion of 20% (very low); literature search of 60% (medium); understand the research design elements 36.67% (low); create a graph of 40% (medium); solving problems by 36.67% (low); understand and interpret basic statistics of 20% (very low); and draw conclusions of 23.33% (low)